Characterization of electromagnetic fluctuations in a HiPIMS plasma. (27th October 2016) - Spagnolo, S; Zuin, M; Cavazzana, R; Martines, E; Patelli, A; Spolaore, M; Colasuonno, M
Abstract: A high power impulse magnetron sputtering (HiPIMS) plasma has been characterized by means of Langmuir probes measuring floating potential, electron temperature and density. Moreover, magnetic sensors have been employed in the analysis of the magnetic fluctuations. A low frequency electro-magnetic structure has been detected to propogate in the HiPIMS plasma at a velocity of about 5 km s −1 in the direction of the E × B drift. It has been characterized in terms of time and space periodicities for different plasma conditions. It exhibits common features with the so-called rotating spokes, observed in various HiPIMS plasmas. The increasing relevance of the electromagnetic nature of the fluctuating structure at high power levels is highlighted.